2019
DOI: 10.1093/ibd/izy383
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: Optimal Salvage Therapy in Acute Severe Ulcerative Colitis

Abstract: BackgroundInfliximab is an effective salvage therapy in acute severe ulcerative colitis; however, the optimal dosing strategy is unknown. We performed a systematic review and meta-analysis to examine the impact of infliximab dosage and intensification on colectomy-free survival in acute severe ulcerative colitis.MethodsStudies reporting outcomes of hospitalized steroid-refractory acute severe ulcerative colitis treated with infliximab salvage were identified. Infliximab use was categorized by dose, dose number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 68 publications
1
54
0
1
Order By: Relevance
“…Furthermore, the need for earlier prediction models is highlighted by the varying practices in relation to timing and selection of patients for rescue therapies. 5 I also agree with Drs. Laharie and Riviere on the lack of evidence for proposing accelerated induction regimens in ASUC as seen in the two recent updated meta-analyses of observational studies.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Furthermore, the need for earlier prediction models is highlighted by the varying practices in relation to timing and selection of patients for rescue therapies. 5 I also agree with Drs. Laharie and Riviere on the lack of evidence for proposing accelerated induction regimens in ASUC as seen in the two recent updated meta-analyses of observational studies.…”
supporting
confidence: 73%
“…6,7 Nevertheless, the recently published UK IBD guidelines 8 recommend its use in this setting and, based on national surveys, the use of accelerated induction is frequent. 5,9 The ongoing prospective studies may provide us with more robust evidence to settle this important debate.Until then, physicians should use their judgement based on available risk prediction models and involve patients and colorectal surgeons in shared decision-making when choosing their treatment approach.…”
mentioning
confidence: 99%
“…We also agree that almost all of the cohort studies so far have not reported data to support the use of accelerated induction dosing regimens despite compelling pharmacokinetic and pharmacodynamic data. 3 In the recent systematic review from Choy et al, 4 while multiple dosing of infliximab was better than a single dose in reducing colectomy, there was no benefit in any of the intensive dosing regimes (more frequent doses of 5 mg/kg or higher front loading dose of 10 mg/kg) in short-term or long-term colectomy rates. This is similar to the findings from our own meta-analysis which failed to show a benefit from intensified dosing.…”
mentioning
confidence: 99%
“…In particular no significant difference in early or late colectomy rates has been found between accelerated and standard regimens in two recent systematic reviews. 2,3 Clinicians' perception of disease severity often drives the selection of standard vs accelerated therapy. Sebastian et al 1 are to be commended for their use of propensity scoring analysis in their study as a means of addressing provider bias.…”
mentioning
confidence: 99%